COX-2 expression in mammary invasive micropapillary carcinoma is associated with prognostic factors and acts as a potential therapeutic target in comparative oncology - Vieira, Thaynan Cunha; Oliveira, Evelyn Ane; Santos, Bárbara Jaime dos; Souza, Fernanda Rezende; Veloso, Emerson Soares; Nunes, Cristiana Buzelin; Del Puerto, Helen Lima; Cassali, Geovanni Dantas (Frontiers in Veterinary Science, 2022)
Pure human and canine mammary invasive micropapillary carcinoma is a rare malignant epithelial tumor accounting for 0.9 to 2% of all invasive mammary carcinomas and present a high rate of lymphatic invasion and metastasis, with unfavorable prognosis. Surgery and chemotherapy are standard treatments for almost all mammary cancer in both species, as well as hormonal and target therapies available for human patients. However, depending on the patient's clinical staging, satisfactory therapeutic results for invasive micropapillary carcinoma are a challenge due to its high capacity of invasion and metastasis. Cyclooxygenase-2 (COX-2) isoform is an important enzyme stimulated by cytokines, growth factors and oncogenes activation to synthetizes prostaglandins in inflammatory process. COX-2 overexpression is associated with angiogenesis and invasion and contributes to cancer development, disease progression, tumor recurrence and regional lymph node metastasis in human and canine mammary carcinomas. This enzyme can be targeted by non-steroidal anti-inflammatory drugs and its inhibition can reduce tumor growth and metastasis in several cancer types. Given the similarity between both species, the present study aims to elucidate the involvement of COX-2 mRNA and protein expression in canine (cIMPC) and human (hIMPC) pure invasive mammary micropapillary carcinoma, with clinicopathological and survival data. Twenty-nine cases of cIMPC and 17 cases of hIMPC were analyzed regarding histologic type, grade, age, tumor size, lymph node condition, extracapsular extension, inflammatory infiltrate and immunophenotype. When available, information on adjuvant treatment, recurrence, metastasis and overall survival were collected. The present study demonstrated COX-2 protein expression in 65.5% of cIMPC and 92.3% of hIMPC, and an association with more advanced histological grades in bitches and higher Ki67 in women. COX-2 mRNA expression was significantly higher in cIMPC than in hIMPC, and its expression was not associated with COX-2 protein expression in both species. COX-2 mRNA expression was associated with negative-ER hIMPC as well as higher Ki67. cIMPC demonstrated proportional early development, more regional metastasis, and a prevalence of negative estrogen receptor, than hIMPC. This is the first time COX-2 expression is associated with negative prognostic factors in both cIMPC and hIMPC, besides the overexpression of COX-2 protein in such unfavorable histological type, which suggests that COX-2 can act as a potential target in IMPC.